2012
DOI: 10.1017/s0007114512003364
|View full text |Cite
|
Sign up to set email alerts
|

Dietary linoleic acid elevates endogenous 2-arachidonoylglycerol and anandamide in Atlantic salmon (Salmo salarL.) and mice, and induces weight gain and inflammation in mice

Abstract: Dietary intake of linoleic acid (LA) has increased dramatically during the twentieth century and is associated with a greater prevalence of obesity. Vegetable oils are recognised as suitable alternatives to fish oil (FO) in feed for Atlantic salmon (Salmo salar L.) but introduce high amounts of LA in the salmon fillet. The effect on fish consumers of such a replacement remains to be elucidated. Here, we investigate the effect of excessive dietary LA from soyabean oil (SO) on endocannabinoid levels in Atlantic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 68 publications
5
62
1
2
Order By: Relevance
“…Evidence has accumulated indicating a tonic overactivation of ECS after HFD-induced obesity (14,35,47). Nevertheless, data from the literature (12,14,48) also suggest that the effect of HFD feeding on peripheral EC levels may depend on the FA composition of the diet. In the current study, we consistently observed that tissue EC contents were generally higher after long-term administration of an HFD, whatever the early LFD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has accumulated indicating a tonic overactivation of ECS after HFD-induced obesity (14,35,47). Nevertheless, data from the literature (12,14,48) also suggest that the effect of HFD feeding on peripheral EC levels may depend on the FA composition of the diet. In the current study, we consistently observed that tissue EC contents were generally higher after long-term administration of an HFD, whatever the early LFD.…”
Section: Discussionmentioning
confidence: 99%
“…AA is endogenously biosynthesized from the essential FA (10) linoleic acid (LA [or C18:2n-6]). As a consequence, a dietary supplementation in LA (11,12) or AA itself (13) is able to elevate the tissue contents of EC. Conversely, diets enriched with n-3 polyunsaturated FAs, such as eicosapentaenoic acid (C20:5n-3) and docosahexaenoic acid (DHA [or C22:6n-3]), cause a decrease in 2-AG and AEA levels because of the replacement of AA in phospholipids with such FAs (13,14).…”
mentioning
confidence: 99%
“…Furthermore, a similar trend was exhibited with DHEA/OEA and percent android fat, indicating that OEA levels have less affi nity for android fat distribution when compared with both AEA and DHEA. It has been identifi ed that the effect of AEA on weight gain can be reduced with the inclusion of dietary EPA and DHA and can reduce visceral fat mass in rats ( 15,30,31 ), thus the observation that DHEA, the NAE-analog of DHA, was correlated with android fat deposition more so than OEA suggests that circulating OEA levels may contribute to a more desirable regional body fat deposition profi le than do other NAEs. Moreover, it was also observed that plasma NAE levels exhibited a moderate direct correlation with carbohydrate oxidation but were inversely correlated with fat oxidation, both resting and postprandial, of which plasma AEA levels showed the strongest correlation.…”
Section: Discussionmentioning
confidence: 99%
“…From a human health standpoint, increases in ω6 fatty acids in salmon fillets are a concern. When mice were fed farmed salmon raised on diets with 100% soybean oil, the excessive dietary LA elevated endocannabinoids in the liver, increased weight gain and counteracted the anti-inflammatory properties of EPA and DHA [69] and also exaggerated insulin resistance and increased accumulation of fat in the liver in rats [34]. The typical "Western" diet is already dangerously high in ω6 fatty acids, which is why it is so important to consume fish that are high in ω3 fatty acids to balance this ratio.…”
Section: Fish Nutrition and Human Healthmentioning
confidence: 99%